Site-directed mutagenesis identified the key active site residues of 2,3-oxidosqualene cyclase HcOSC6 responsible for cucurbitacins biosynthesis in Hemsleya chinensis - Li, Xia; Chen, Geng; Gao, Qing-Qing; Xiang, Chun-Fan; Yuan, Cheng-Xiao; Li, Xiao-Ning; Shu, Yan-Yu; Zhang, Guang-Hui; Liang, Yan-Li; Yang, Sheng-Chao; Zhai, Chen-Xi; Zhao, Yan (Frontiers in Plant Science, 2023)
Hemsleya chinensis is a Chinese traditional medicinal plant, containing cucurbitacin IIa (CuIIa) and cucurbitacin IIb (CuIIb), both of which have a wide range of pharmacological effects, including antiallergic, anti-inflammatory, and anticancer properties. However, few studies have been explored on the key enzymes that are involved in cucurbitacins biosynthesis in H. chinensis. Oxidosqualene cyclase (OSC) is a vital enzyme for cyclizing 2,3-oxidosqualene and its analogues. Here, a gene encoding the oxidosqualene cyclase of H. chinensis (HcOSC6), catalyzing to produce cucurbitadienol, was used as a template of mutagenesis. With the assistance of AlphaFold2 and molecular docking, we have proposed for the first time to our knowledge the 3D structure of HcOSC6 and its binding features to 2,3-oxidosqualene. Mutagenesis experiments on HcOSC6 generated seventeen different single-point mutants, showing that single-residue changes could affect its activity. Three key amino acid residues of HcOSC6, E246, M261 and D490, were identified as a prominent role in controlling cyclization ability. Our findings not only comprehensively characterize three key residues that are potentially useful for producing cucurbitacins, but also provide insights into the significant role they could play in metabolic engineering.